The Modern Approach to Virtual Laboratory Workshop - Gubsky, Dmitry S.; Zemlyakov, Viacheslav V.; Mamay, Ivan V. (International Journal of Online and Biomedical Engineering (iJOE), 2014)
The method of computer simulation of microwave measurement units and special laboratory workshop for engineersâ?? education are described. Simulated laboratory has a module structure. The basis for constructing a model of the specific work is a concept of the abstract â??deviceâ? with front panel view and manipulation principles identical to those of the real units.